An in vitro study of mesenchyme–islet cell interactions in islet neogenesis: A model for tissue replacement therapy in diabetes mellitus - Manda, Juziel Kampando (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017